2017
DOI: 10.3171/2016.11.spine16696
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of idiopathic spinal cord herniation from dorsal arachnoid webs on MRI and CT myelography

Abstract: OBJECTIVEDorsal arachnoid webs (DAWs) and spinal cord herniation (SCH) are uncommon abnormalities affecting the thoracic spinal cord that can result in syringomyelia and significant neurological morbidity if left untreated. Differentiating these 2 entities on the basis of clinical presentation and radiological findings remains challenging but is of vital importance in planning a surgical approach. The authors examined the differences between DAWs and idiopathic SCH on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 16 publications
0
40
0
Order By: Relevance
“…The pathologic states of SH are focal ventral or, less commonly, lateral protrusion of part of the cord through the dural defect. Randall et al 9) reviewed the findings on MRI and CT myelography for both AW and SH and found that the scalpel sign was positive in all the patients with AW and that a C-shaped deformity was present in 5 of 6 patients with SH. They also mentioned that the ventral subarachnoid space was preserved in all the patients with AW.…”
Section: Discussionmentioning
confidence: 99%
“…The pathologic states of SH are focal ventral or, less commonly, lateral protrusion of part of the cord through the dural defect. Randall et al 9) reviewed the findings on MRI and CT myelography for both AW and SH and found that the scalpel sign was positive in all the patients with AW and that a C-shaped deformity was present in 5 of 6 patients with SH. They also mentioned that the ventral subarachnoid space was preserved in all the patients with AW.…”
Section: Discussionmentioning
confidence: 99%
“…Both are uncommon conditions and can result in significant neurological morbidity if left untreated. 7 The main aspect is related to the evaluation of the nature of the dorsal cord indentation, as well as the integrity of the ventral subarachnoid space at the level of spinal cord deformity. The "scalpel sign" is usually referred to as pathognomonic for SAW, consisting of dorsal spinal cord indentation and anterior cord displacement.…”
Section: Arachnoid Webs: Preoperative Differential Diagnosis and Surgmentioning
confidence: 99%
“…More recently, the "C-shape dorsal indentation" has been further reported for spinal cord herniation. 7 In practice, differentiating these two separate entities is crucial from a surgical perspective and not always straightforward preoperatively. 7 Their management is different.…”
Section: Arachnoid Webs: Preoperative Differential Diagnosis and Surgmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, the clinical and radiological diagnosis should exclude other pathologies, which might mimic an SAW, in particular thoracic intradural spinal cord herniation (ISCH). Both are uncommon conditions and can result in significant neurological morbidity if left untreated 7 . The main aspect is related to the evaluation of the nature of the dorsal cord indentation, as well as the integrity of ventral subarachnoid space at the level of spinal cord deformity.…”
Section: Dear Editormentioning
confidence: 99%